Hospital-acquired infections in patients hospitalized with COVID-19: First report from Taiwan. Issue 9 (20th June 2022) - Huang, Ruei-Chang; Chiu, Chun-Hsiang; Chiang, Tsung-Ta; Tsai, Chun-Chou; Wang, Yung-Chih; Chang, Feng-Yee; Yang, Ya-Sung; Wang, Ching-Hsun
Abstract : Background: Coronavirus disease 2019 (COVID-19) inpatients may acquire infections from other pathogens during hospital admission. This is the first research on this subject to be reported from Taiwan. Methods: Confirmed COVID-19 inpatients were enrolled in this study from January 1, 2020 to July 31, 2021. Various types of pathogens in COVID-19 inpatients, with hospital-acquired infections, were identified and analyzed. The clinical characteristics of COVID-19 patients with and without hospital-acquired infections were reviewed and compared. Results: Of the 204 patients included in the study, 32 (15.7%) patients experienced at least one infectious episode. Of 113 recorded episodes of infection, the predominant type was bacterial (88 of 113 infections, 77.9%); the most frequently isolated bacteria were Acinetobacter spp., followed by Stenotrophomonas maltophilia . With regard to viral infections (19 of 113, 16.8%), the Epstein-Barr virus ranked first place among the identified viruses. Four (3.5%) and 2 (1.8%) of 113 infectious episodes were caused by fungi and atypical pathogens. A multivariate analysis revealed that steroid use was an independent factor in hospital-acquired infections (odds ratio [OR], 6.97; 95% confidence interval [CI], 1.15–42.43; p = 0.035). Patients with hospital-acquired infections were associated with increased 28-day and in-hospital mortality (18.8% vs 5.8% and 31.3% and 5.8%; p = 0.023 and <0.01, respectively), and a longer hospital stay (34 vs 19 days; p < 0.001), compared to those without hospital-acquired infections. Conclusion: Our study revealed the unique local epidemiology of hospital-acquired infections among COVID-19 inpatients in Taiwan. These patients were associated with increased mortality and prolonged hospital admissions.